Long QT Syndrome: An Emerging Role for Inflammation and Immunity - Lazzerini, Pietro Enea; Capecchi, Pier Leopoldo; Laghi-Pasini, Franco (Frontiers in Cardiovascular Medicine, 2015)
The Long QT Syndrome (LQTS), classified as congenital or acquired, is a multi-factorial disorder of myocardial repolarization predisposing to life-threatening ventricular arrhythmias, particularly torsades de pointes. In the latest years inflammation and immunity have been increasingly recognized as novel factors crucially involved in modulating ventricular repolarization. In the present paper we critically review the available information on this topic, also analyzing putative mechanisms and potential interplays with the other etiologic factors, either acquired and inherited. Accumulating data indicate inflammatory activation as a potential cause of acquired LQTS. The putative underlying mechanisms are complex but essentially cytokine-mediated, including both direct actions on cardiomyocyte ion channels expression and function, and indirect effects resulting from an increased central nervous system sympathetic drive on the heart. Autoimmunity represents another recently arising cause of acquired LQTS. Indeed, increasing evidence demonstrates that autoantibodies may affect myocardial electric properties by directly cross-reacting with the cardiomyocyte and interfering with specific ion currents as a result of molecular mimicry mechanisms. Intriguingly, recent data suggest that inflammation and immunity may be also involved in modulating the clinical expression of congenital forms of LQTS, possibly triggering or enhancing electrical instability in patients who already are genetically predisposed to arrhythmias. In this view, targeting immuno-inflammatory pathways may in the future represent an attractive therapeutic approach in a number of LQTS patients, thus opening new exciting avenues in antiarrhythmic therapy.